Lithium-sulfur battery catalyst, preparation method and application thereof
Patent Information
- Application Number
- CN202511722814.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-21
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-11-21
AI Technical Summary
现有研究证实,将碳量子点负载于碳纳米管表面引入锂硫电池,可强化对硫的吸附固定效果,但目前关于碳量子点与其他金属化合物复合形成协同体系,作为锂硫电池电催化剂以同步优化吸附性能与催化活性的研究仍较为匮乏
本发明通过将锂硫电池催化剂材料和硫宿主材料相结合,提出一种核壳结构催化剂材料的合成方法。该核壳材料的核为氧化铜,壳由碳量子点修饰的四氧化三钴组成。在硫物种进行氧化还原的过程中,核结构能壳内移动,起到了动态催化的作用,进一步提高了催化性能。除此之外,该核壳结构有大量空间用于包覆活性硫,能够物理固定硫物种,抑制了穿梭效应;牢固的过渡金属化合物外壳还能够缓冲充放电过程中硫物种转化带来的体积变化,减小对正极片的形貌的破坏,大大提升了电池的长循环性能。除此之外,碳量子点的加入可从抑制多硫化物的穿梭效应、催化多硫化物转化、提升硫正极的导电性等多个方面进一步提高锂硫电池的电化学性能。本发明中的锂硫电池催化剂结构稳定,工艺简单,成本低廉,应用前景广阔。
Smart Images

Figure CN121534710B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-sulfur battery technology, and in particular to a lithium-sulfur battery catalyst, its preparation method, and its application. Background Technology
[0002] Lithium-ion batteries (LIBs) are gradually approaching their energy density limits, making it difficult to meet the rapidly growing energy storage demands of electric vehicles, large-scale energy storage devices, and advanced portable electronic devices. Lithium-sulfur batteries (Li-S), with their advantages of high natural abundance of sulfur as the active material, low cost, and environmental friendliness, and high energy density of up to 1675 mAh / g, offer a more competitive alternative. -1 With its theoretical specific capacity, it exhibits an overwhelming advantage in energy density and is widely recognized as a highly promising candidate for next-generation electrochemical energy storage technology.
[0003] However, the application of lithium-sulfur batteries still faces many key technological bottlenecks, which severely restrict their performance improvement: Firstly, elemental sulfur and the discharge end product lithium sulfide (Li2S / Li2S2) are both insulators, and the diffusion rate of lithium ions in lithium sulfide is only 10. -15 cm 2 ·s -1 First, the electrochemical reaction kinetics are slowed down. Second, the long-chain polysulfides generated during charging and discharging are easily soluble in the electrolyte, passing through the separator and shuttling back and forth between the positive and negative electrodes, causing the "shuttle effect," which leads to lithium metal corrosion, decreased coulombic efficiency, and loss of active materials. Third, the density difference between S8 and Li2S is large, and the repeated conversion between the two during charging and discharging causes changes in electrode volume, destroys the integrity of the electrode structure, and affects the safe operation of the battery. Fourth, the uneven distribution of lithium ion concentration on the surface of the lithium metal negative electrode easily forms lithium dendrites, which may puncture the separator and cause a short circuit in the battery in severe cases.
[0004] To address these issues, researchers have conducted extensive studies across multiple dimensions, including the cathode, anode, separator, and electrolyte. Among these, designing modified sulfur cathode materials is the most common and effective improvement direction. On one hand, developing sulfur supports with adsorption capabilities can immobilize polysulfides and suppress the shuttle effect. Some literature has revealed through theoretical calculations the moderate adsorption effect of two-dimensional layered materials on polysulfides, effectively immobilizing them while maintaining their structural integrity. Other literature has found that polar Co9S8 can immobilize polysulfides through strong chemisorption, significantly reducing their loss. Carbon-based materials, due to their high specific surface area, can enhance the conductivity of sulfur electrodes, promote sulfur electrochemical conversion, and physically limit polysulfide loss. Furthermore, by modulating the surface electronic structure through heteroatoms, the chemisorption of polysulfides can be further enhanced, accelerating reaction kinetics. For example, some literature has confirmed that N and S-doped porous graphene networks possess excellent electrocatalytic activity for sulfur reduction reactions, improving battery rate performance and cycle stability. On the other hand, high-performance sulfur supports also need to have catalytic activity to enhance the kinetics of sulfur conversion reactions. Some literature has shown that the "fixation-conversion" synergistic mechanism has confirmed that the thiophilic CoS2 has both good chemical affinity for polysulfides and the effect of enhancing reaction kinetics. Other literature reports that when lithium-ionized MoS2 nanosheets are used as sulfur supports, they can enhance lithium-ion transport and significantly improve the kinetics of sulfur conversion reactions.
[0005] Carbon quantum dots, as a special type of carbon-based material, not only possess the basic properties of bulk carbon materials but also have unique advantages such as fast electron transport rate, strong adsorption capacity, high stability, simple synthesis and preparation, environmental friendliness, and easily tunable structure (e.g., heteroatom doping, surface modification), making them potential candidates for high-performance sulfur supports. Existing research has confirmed that loading carbon quantum dots onto the surface of carbon nanotubes and introducing them into lithium-sulfur batteries can enhance the adsorption and fixation of sulfur. However, research on the formation of synergistic systems using carbon quantum dots in combination with other metal compounds as electrocatalysts in lithium-sulfur batteries to simultaneously optimize adsorption performance and catalytic activity remains relatively scarce.
[0006] Therefore, developing a novel lithium-sulfur battery catalyst that achieves the synergistic effect of efficient adsorption and fixation of polysulfides and rapid catalytic conversion through reasonable structural design, thereby improving the catalytic conversion kinetics of sulfur cathode, improving sulfur utilization, and ultimately enhancing the specific capacity and cycle stability of lithium-sulfur batteries, has become a key factor in promoting the commercial application of lithium-sulfur batteries and has significant research value and application prospects. Summary of the Invention
[0007] The purpose of this invention is to provide a lithium-sulfur battery catalyst, its preparation method, and its application, so as to improve the catalytic conversion kinetics of sulfur cathode, improve sulfur utilization, and enhance the specific capacity and cycle stability of lithium-sulfur batteries.
[0008] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing a lithium-sulfur battery catalyst, comprising the following steps: (1) Disperse cuprous oxide, surfactant, cobalt source and sodium thiosulfate solution in solvent and react to obtain cobalt hydroxide / cuprous oxide core-shell catalyst; (2) The cobalt hydroxide / cuprous oxide core-shell catalyst was heat-treated in air atmosphere to obtain cobalt tetroxide / copper oxide core-shell catalyst; (3) Mix cobalt tetroxide / copper oxide core-shell catalyst, carbon quantum dots and water, and carry out hydrothermal reaction to obtain lithium-sulfur battery catalyst.
[0009] Optionally, the cuprous oxide is cubic hexahedral in shape; the cuprous oxide has a particle size of 300-500 nm; the cobalt source includes cobalt chloride or cobalt nitrate; the surfactant includes polyvinylpyrrolidone; the solvent is a mixture of water and ethanol; and the volume ratio of water to ethanol is 1:1-3.
[0010] Optionally, the mass ratio of cuprous oxide to cobalt source is 1.6~1.7:1; The mass ratio of the surfactant to cuprous oxide is 1:0.08~0.12; The concentration of the sodium thiosulfate solution is 1 mol / L; the ratio of the cobalt source to the sodium thiosulfate solution is 220 mg: 40~120 mL; and the volume ratio of the sodium thiosulfate solution to the solvent is 0.4~1.2:1.
[0011] Optionally, the reaction in step (1) is carried out at room temperature for 20 to 40 minutes.
[0012] Optionally, the heat treatment temperature is 350~550℃, the time is 2~4h, and the heating rate is 3~5℃ / min.
[0013] Optionally, the carbon quantum dots account for 3 to 10% of the mass of the cobalt tetroxide / copper oxide core-shell structure catalyst.
[0014] Optionally, the hydrothermal reaction is carried out at a temperature of 120~160℃ for 8~24 hours.
[0015] The present invention also provides a lithium-sulfur battery catalyst prepared by the above-described preparation method.
[0016] The present invention also provides a lithium-sulfur battery comprising the above-described lithium-sulfur battery catalyst.
[0017] Optionally, the lithium-sulfur battery catalyst is added to the sulfur cathode of the lithium-sulfur battery.
[0018] Compared with the prior art, the present invention has the following beneficial effects: This invention proposes a method for synthesizing a core-shell structured catalyst material by combining a lithium-sulfur battery catalyst material with a sulfur host material. The core of this core-shell material is copper oxide, and the shell is composed of cobalt tetroxide modified with carbon quantum dots. During the redox process of sulfur species, the core structure can move within the shell, playing a dynamic catalytic role and further improving catalytic performance. In addition, this core-shell structure provides ample space for encapsulating active sulfur, physically immobilizing sulfur species and suppressing the shuttle effect; the robust transition metal compound shell also buffers the volume changes caused by sulfur species transformation during charge and discharge, reducing damage to the morphology of the cathode and significantly improving the long-cycle performance of the battery. Furthermore, the addition of carbon quantum dots can further improve the electrochemical performance of lithium-sulfur batteries from multiple aspects, such as suppressing the shuttle effect of polysulfides, catalyzing polysulfide transformation, and improving the conductivity of the sulfur cathode. The lithium-sulfur battery catalyst of this invention has a stable structure, simple process, low cost, and broad application prospects. Attached Figure Description
[0019] Figure 1 Here is a SEM image of the cuprous oxide prepared in this invention; Figure 2 The XRD pattern of cuprous oxide prepared in this invention; Figure 3 Here is a SEM image of the hollow structure of Co(OH)2 in Example 1; Figure 4 This is a SEM image of the Cu2O@Co(OH)2 core-shell structure from Example 2. Figure 5 This is a SEM image of the Cu2O@Co(OH)2 core-shell structure from Example 3; Figure 6 Charge-discharge curves of the electrode and SC positive electrode prepared by CuO@Co3O4 / CQDs of the present invention; Figure 7 Cyclic performance curves of the electrode and SC cathode prepared by CuO@Co3O4 / CQDs of the present invention; Figure 8 Electrochemical impedance spectroscopy of the electrode and SC cathode prepared by CuO@Co3O4 / CQDs of the present invention; Figure 9 Rate performance diagrams of the electrodes and SC cathodes prepared by CuO@Co3O4 / CQDs according to the present invention. Detailed Implementation
[0020] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0021] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0022] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0023] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be obvious to those skilled in the art. This application specification and embodiments are merely exemplary.
[0024] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0025] All raw materials used in this invention can be obtained commercially or prepared using existing technologies.
[0026] The room temperature involved in this invention is 25±2℃.
[0027] This invention provides a method for preparing a lithium-sulfur battery catalyst, comprising the following steps: (1) Disperse cuprous oxide, surfactant, cobalt source and sodium thiosulfate solution in solvent and react to obtain cobalt hydroxide / cuprous oxide core-shell catalyst; (2) The cobalt hydroxide / cuprous oxide core-shell catalyst was heat-treated in air atmosphere to obtain cobalt tetroxide / copper oxide core-shell catalyst; (3) Mix cobalt tetroxide / copper oxide core-shell catalyst, carbon quantum dots and water, and carry out hydrothermal reaction to obtain lithium-sulfur battery catalyst.
[0028] This invention involves dispersing a surfactant in a solvent, then adding cuprous oxide and a cobalt source and ultrasonically dispersing for 30 minutes. After uniform dispersion, sodium thiosulfate solution is added dropwise under vigorous stirring, and the reaction is continued with stirring. The product obtained from the reaction is washed three times by centrifugation with water and ethanol, and then dried overnight in a vacuum oven at 60°C to obtain a cobalt hydroxide / cuprous oxide core-shell catalyst.
[0029] In some embodiments of the present invention, the method for preparing cuprous oxide includes the following steps: Copper nitrate and water were mixed, then sodium hydroxide solution was added, followed by ascorbic acid solution, and the reaction was carried out to obtain brick-red cuprous oxide powder. The ratio of copper nitrate to water is 1.315 g: 300 mL; the mixing temperature of copper nitrate and water is 50 °C, and the mixing time is 30 min; the concentration of sodium hydroxide solution is 3 mol / L, and the volume ratio of sodium hydroxide solution to water is 1:6; the sodium hydroxide solution is added dropwise to the aqueous solution of copper nitrate, and the mixture is stirred for 30 min after addition; the concentration of ascorbic acid solution is 3 mol / L, and the volume ratio of ascorbic acid solution to sodium hydroxide solution is 1:1; the reaction temperature is 50 °C, and the reaction time is 3 h. After the reaction was completed, the product was washed three times by centrifugation with water and ethanol and then dried in a vacuum oven at 60°C overnight. To prevent oxidation of the cuprous oxide precursor, the cuprous oxide powder was stored in a glove box filled with argon gas. The cuprous oxide has a cubic hexahedral shape and a particle size of 300~500nm.
[0030] In this invention, the cobalt source includes cobalt chloride or cobalt nitrate, preferably cobalt chloride; the surfactant includes polyvinylpyrrolidone (PVP); the solvent is a mixture of water and ethanol; the volume ratio of water to ethanol is 1:1 to 3, for example, 1:1, 1:2 or 1:3, etc.
[0031] In this invention, the mass ratio of cuprous oxide to cobalt source is 1.6~1.7:1, preferably 18:11; The mass ratio of the surfactant to cuprous oxide is 1:0.08~0.12, for example, it can be 1:0.08, 1:0.1 or 1:0.12, etc.; The concentration of the sodium thiosulfate solution is 1 mol / L; the volume ratio of the cobalt source to the sodium thiosulfate solution is 220 mg: 40~120 mL. For example, it can be 220 mg: 40 mL, 220 mg: 50 mL, 220 mg: 60 mL, 220 mg: 80 mL, 220 mg: 100 mL, or 220 mg: 120 mL, etc.; the volume ratio of the sodium thiosulfate solution to the solvent is 0.4~1.2:1, for example, it can be 0.4:1, 0.6:1, 0.8:1, 1:1, or 1.2:1, etc.
[0032] Understandably, the d-electron orbitals of transition metals can interact with the lone pairs of electrons in LiPSs to form chemical bonds (such as MS bonds), enhancing the adsorption of soluble LiPSs and lowering the reaction energy barrier. Therefore, transition metal compounds are an effective class of catalysts and adsorbents for lithium-sulfur batteries, significantly improving sulfur utilization and cycle stability through multiple mechanisms such as chemisorption, redox-mediated processes, and interfacial modulation. Meanwhile, copper oxide / cuprous oxide, as the core, is also widely used as a catalyst and adsorbent in lithium-sulfur batteries. Therefore, the core-shell structured catalyst prepared in this invention has a copper oxide core and a carbon quantum dot-modified cobalt tetroxide shell. During the redox process of sulfur species, the core structure can move within the shell, playing a dynamic catalytic role and further improving catalytic performance.
[0033] In this invention, the reaction temperature in step (1) is room temperature and the time is 20~40 min, for example, it can be 20 min, 30 min or 40 min.
[0034] In this invention, the heat treatment temperature is 350~550℃, for example, 350℃, 400℃, 500℃ or 550℃, etc., the time is 2~4h, for example, 2h, 3h or 4h, etc., and the heating rate is 3~5℃ / min, for example, 3℃ / min, 4℃ / min or 5℃ / min, etc.
[0035] This invention disperses a cobalt tetroxide / copper oxide core-shell structure catalyst in water, then adds carbon quantum dot powder, loads it into a hydrothermal reactor and keeps it at a constant temperature. After the hydrothermal reaction is completed, the product is filtered, centrifuged and dried to obtain a lithium-sulfur battery catalyst.
[0036] In this invention, the carbon quantum dots account for 3 to 10% of the mass of the cobalt tetroxide / copper oxide core-shell structure catalyst, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%.
[0037] In this invention, the temperature of the hydrothermal reaction is 120~160℃, for example, it can be 120℃, 130℃, 140℃, 150℃ or 160℃, etc., and the time is 8~24h, for example, it can be 8h, 10h, 12h, 16h, 18h or 24h, etc.
[0038] In some embodiments of the present invention, the preparation method of the carbon quantum dots includes: washing and drying leaves or plant stems and leaves, crushing and sieving them to obtain raw materials; subjecting the raw materials to heat treatment; after the heat treatment is completed, cooling the reaction products and dissolving them in water; removing large particulate impurities by filtration; and then purifying them by dialysis to obtain carbon quantum dots. The leaves include pothos leaves or sycamore leaves; the sieving is done through an 80-mesh sieve; the heat treatment temperature is 500℃ and the time is 3 hours. This invention uses dead tree leaves as a carbon source to synthesize carbon quantum dots, and the types of dead tree leaves can be adjusted. Carbon quantum dots have the advantages of high yield, low cost, and large-scale application.
[0039] The present invention also provides a lithium-sulfur battery catalyst prepared by the above-described preparation method.
[0040] Understandably, this invention proposes a lithium-sulfur battery catalyst composed of a core-shell structure that serves as both a catalyst material and a sulfur host material, combined with carbon quantum dots.
[0041] The present invention also provides a lithium-sulfur battery comprising the above-described lithium-sulfur battery catalyst.
[0042] In this invention, the lithium-sulfur battery catalyst is added to the sulfur cathode of the lithium-sulfur battery.
[0043] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0044] Preparation Example 1 Dissolve 1.315 g of copper nitrate pentahydrate in 300 mL of deionized water, heat and stir in a water bath at 50 °C for 30 minutes, then add 50 mL of 3 mol / L sodium hydroxide solution dropwise, continue stirring for 30 minutes, then add 50 mL of 3 mol / L ascorbic acid solution dropwise, continue heating and stirring for 3 hours, the product is washed three times by centrifugation with water and ethanol, and then dried overnight in a vacuum oven at 60 °C to obtain brick-red cuprous oxide powder.
[0045] To prevent the precursor from oxidizing, cuprous oxide powder was stored in an argon-filled glove box.
[0046] Weigh 5 mg of cubic cuprous oxide precursor and place it in a centrifuge tube. Add 5 mL of ethanol and sonicate for 30 minutes to disperse it evenly. Use a pipette to add an appropriate amount of the ethanol dispersion to the glossy surface of a silicon wafer. Dry the silicon wafer to obtain a SEM sample and take a scanning electron microscope image. Figure 1 This shows that cuprous oxide with a cubic hexahedral structure was successfully synthesized.
[0047] Figure 2 This is the XRD pattern of cuprous oxide prepared in this invention. Figure 2 It can be seen that the peak position of the cuprous oxide curve prepared by the present invention completely coincides with the standard curve, indicating that the present invention has successfully synthesized cuprous oxide, and the sample has high purity and good crystallization.
[0048] Preparation Example 2 Raw material pretreatment: The leaves of the paulownia tree are washed, dried and then crushed and passed through an 80-mesh sieve to obtain uniform powder; Solventricular synthesis: The precursor is placed in a tube furnace reaction vessel and heated at 500°C for 3 hours. After cooling, the reaction product is dissolved in water, and large particulate impurities are removed by filtration and then purified by dialysis to obtain carbon quantum dots.
[0049] Example 1 3g of PVP was weighed and dissolved in 100mL of solution (water:ethanol = 1:1). Then, 360mg of cubic cuprous oxide (preparation example 1) and 220mg of cobalt chloride hexahydrate were weighed and placed in the solution. The mixture was sonicated for 30 minutes to disperse it completely. 120mL of 1mol / L sodium thiosulfate solution was added dropwise under vigorous stirring. After reacting for 40 minutes, the solution turned light green. The product was washed three times by centrifugation with water and ethanol and then dried overnight in a vacuum oven at 60℃ to obtain the hollow Co(OH)2 catalyst, which was designated as sample ①.
[0050] Example 2 3g of PVP was dissolved in 100mL of water:ethanol = 1:1 solution. Then, 360mg of cubic cuprous oxide (Preparation Example 1) and 220mg of cobalt chloride hexahydrate were weighed and added to the solution. The mixture was sonicated for 30 minutes to ensure complete dispersion. 40mL of 1mol / L sodium thiosulfate solution was added dropwise under vigorous stirring. After reacting for 10 minutes, the solution turned yellow-green. The obtained product was washed three times by centrifugation with water and ethanol and then dried overnight in a vacuum oven at 60℃ to obtain the cobalt hydroxide / cuprous oxide core-shell catalyst (Cu2O@Co(OH)2 core-shell catalyst), designated as sample ②.
[0051] Example 3 3g of PVP was dissolved in 100mL of water:ethanol = 1:1 solution. Then, 360mg of cubic cuprous oxide (Preparation Example 1) and 220mg of cobalt chloride hexahydrate were weighed and added to the solution. The mixture was sonicated for 30 minutes to ensure complete dispersion. 60mL of 1mol / L sodium thiosulfate solution was added dropwise under vigorous stirring. After reacting for 20 minutes, the solution turned light yellow-green. The product was washed three times by centrifugation with water and ethanol and then dried overnight in a vacuum oven at 60℃ to obtain the cobalt hydroxide / cuprous oxide core-shell catalyst (Cu2O@Co(OH)2 core-shell catalyst), designated as sample ③.
[0052] Test Example 1 Samples ①, ②, and ③ were placed in centrifuge tubes, and 5 mL of ethanol was added to each. The tubes were then sonicated for 30 minutes to ensure uniform dispersion. A suitable amount of the ethanol dispersion was then pipetted onto the glossy surface of a silicon wafer. The wafer was dried to obtain the SEM sample, and scanning electron microscope images were taken.
[0053] Figure 3 The image shows a SEM image of the hollow structure of Co(OH)₂ prepared in Example 1. Figure 3 It can be seen that the structure is a hollow nanostructure. Due to the etching effect of sodium thiosulfate solution, after 40 minutes of reaction, cuprous oxide was completely etched, and the internal core structure disappeared, and only a hollow Co(OH)2 structure was formed. This result shows that regulating the content of sodium thiosulfate solution and etching time plays a key role in obtaining an effective core-shell structure. Figure 4 This is a SEM image of the Cu2O@Co(OH)2 core-shell structure prepared in Example 2. Figure 4 It can be seen that, due to the significant reduction in the content of sodium thiosulfate solution and etching time, the resulting core-shell structure has a larger core, which is not conducive to the adsorption and catalysis of active sulfur in the later stage. Figure 5 This is a SEM image of the Cu2O@Co(OH)2 core-shell structure prepared in Example 3. Figure 5 It can be seen that the obtained core-shell structure is uniform, the internal core structure can realize dynamic catalysis, and the outer shell structure has a large specific surface area, which can realize effective sulfur adsorption nuclear catalysis. This result indicates that a good core-shell structure can be obtained with appropriate sodium thiosulfate solution content and etching time.
[0054] Example 4 In an air atmosphere, the cobalt hydroxide / cuprous oxide core-shell catalyst prepared in Example 3 was heated to 400°C at a rate of 5°C / min and held at that temperature for 2 hours to obtain the cobalt tetroxide / copper oxide core-shell catalyst.
[0055] Example 5 100 mg of the cobalt tetroxide / copper oxide core-shell structure catalyst from Example 4 was ultrasonically dispersed in 50 mL of deionized water, and then 5% of the sample mass of carbon quantum dots (Preparation Example 2) was added. The mixture was placed in a hydrothermal reactor and reacted at 140 °C for 12 h. The resulting product was filtered, centrifuged, and dried to obtain the composite catalyst, labeled as: CuO@Co3O4 / CQDs.
[0056] Test Example 2 Preparation of sulfur composite electrode: The obtained catalyst material was mixed with elemental sulfur at a mass ratio of 3:7 and kept at 155°C in a reactor for 12 hours. A conductive agent and a binder were added to the resulting composite electrode at a mass ratio of 8:1:1. The mixture was then added to N-methylpyrrolidone (NMP) solvent and stirred to prepare an electrode slurry. The obtained slurry was coated onto an aluminum foil surface, dried, and then cut into small electrode discs for coin cell testing.
[0057] Electrochemical testing: A coin cell was used to study the catalytic conversion of sulfur. A composite sulfur electrode was used as the positive electrode, and lithium metal as the negative electrode. A PP membrane was used as the separator. The electrolyte was a 1M LiTFSI salt dissolved in a solution of 1,3-dioxolane (DOL) and dimethyl ether (DME). All tests were conducted at 25°C. The charge / discharge test voltage range was 1.7–2.8 V. The capacity and cycle testing rate was 0.2 C, and the current density for rate testing was 0.2–2 C. Electrochemical impedance spectroscopy was performed at frequencies from 0.1 Hz to 200 kHz.
[0058] Figure 6 The image shows the charge-discharge curves of the electrodes prepared by CuO@Co3O4 / CQDs according to the present invention. Figure 7 This is a cycling performance curve of the electrode prepared by CuO@Co3O4 / CQDs according to the present invention. Figure 6 and Figure 7 It is evident that the electrode with the catalyst of this invention exhibits stronger cycle stability and greater specific capacity.
[0059] Figure 8 This is a comparison of the electrochemical impedance spectroscopy between the sulfur cathode material prepared by CuO@Co3O4 / CQDs of this invention and the SC cathode. Figure 8 It can be seen that the catalyst prepared by the present invention significantly improves the reaction kinetics of Li-S batteries and exhibits a smaller charge transfer resistance (smaller semicircle).
[0060] Figure 9 This is a comparison chart of the rate performance of the sulfur cathode material prepared by CuO@Co3O4 / CQDs and the SC cathode according to the present invention. Figure 9It can be seen that the catalyst material effectively improves the rate performance of the sulfur cathode. At various rates from 0.2 to 2C, the battery capacity is significantly improved, demonstrating the catalytic effect of the catalyst on accelerating the sulfur conversion reaction, effectively promoting electrochemical reaction kinetics and inhibiting the shuttle effect of polysulfides.
[0061] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a lithium-sulfur battery catalyst, characterized in that, Includes the following steps: (1) Disperse cuprous oxide, surfactant, cobalt source and sodium thiosulfate solution in solvent and react to obtain cobalt hydroxide / cuprous oxide core-shell catalyst; (2) The cobalt hydroxide / cuprous oxide core-shell catalyst was heat-treated in air atmosphere to obtain cobalt tetroxide / copper oxide core-shell catalyst; (3) Mix cobalt tetroxide / copper oxide core-shell catalyst, carbon quantum dots and water, and carry out hydrothermal reaction to obtain lithium-sulfur battery catalyst; The cuprous oxide has a cubic hexahedral shape and a particle size of 300-500 nm. The mass ratio of cuprous oxide to cobalt source is (1.6~1.7):1; The mass ratio of the surfactant to cuprous oxide is 1:(0.08~0.12). The concentration of the sodium thiosulfate solution is 1 mol / L; the ratio of the cobalt source to the sodium thiosulfate solution is 220 mg: (40~120) mL; the volume ratio of the sodium thiosulfate solution to the solvent is (0.4~1.2):1; The heat treatment temperature is 350~550℃, the time is 2~4h, and the heating rate is 3~5℃ / min; The reaction in step (1) is carried out at room temperature for 20-40 minutes.
2. The preparation method according to claim 1, characterized in that, The cobalt source includes cobalt chloride or cobalt nitrate; the surfactant includes polyvinylpyrrolidone; the solvent is a mixture of water and ethanol; and the volume ratio of water to ethanol is 1:(1~3).
3. The preparation method according to claim 1, characterized in that, The carbon quantum dots account for 3% to 10% of the mass of the cobalt tetroxide / copper oxide core-shell structure catalyst.
4. The preparation method according to claim 1, characterized in that, The hydrothermal reaction is carried out at a temperature of 120~160℃ for 8~24 hours.
5. The lithium-sulfur battery catalyst prepared by the preparation method according to any one of claims 1 to 4.
6. A lithium-sulfur battery, characterized in that, It includes the lithium-sulfur battery catalyst as described in claim 5.
7. The lithium-sulfur battery according to claim 6, characterized in that, The lithium-sulfur battery catalyst is added to the sulfur cathode of a lithium-sulfur battery.
Citation Information
Patent Citations
Copper oxide nanometer rod loaded with cobaltosic oxide and synthesis method thereof
CN106145179A
Preparation method of cuprous oxide-cobaltosic oxide core-shell material for electrocatalytic hydrolysis and product of preparation method
CN108452804A
Preparation method of cobaltosic oxide and carbon quantum dot composite material
CN113437307A